Water behavior based electric generation via charge separation. (April 2021) - Chung, Jihoon; Heo, Deokjae; Shin, Gunsub; Chung, Seh-Hoon; Hong, Jinkee; Lee, Sangmin
Abstract: Recent studies have used water droplets to generate electricity with a substantial power output of 50.1 Wm −2 . However, the generation mechanism resulting in this high output is unclear, because only the solid–water interface is considered and water is considered to act only as a charge carrying medium. This paper reports on the generation of electricity via the charge separation of water. The charge separation owing to water movement and impact leads to an extensive accumulation of electrical charge in water. A high electric power output is generated when mobile water carrying the accumulated charge comes in contact with a metal surface. These findings serve as a basis for establishing a correlation between charge separation and electricity generation based on water. Graphical Abstract: ga1 Highlights: First report of water-based electricity generation mechanism by charge separation of water. High-output electric generation up to instantaneous power of 26.6 mW. Electric output analysis depending on ionic and molecular solutions.